Bantengan Art and Ideology: The Independent Banteng Dance as a Spirit of Freedom - Belinda Dewi Regina; Suharto Suharto; Wandah Wibawanto (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2024)
Bantengan art, as part of East Javanese traditional culture, not only functions as entertainment, but also as a medium for social and ideological expression that is full of symbolic meaning. This research aims to analyze the relationship between Bantengan art and the ideology of freedom, with a focus on the Merdeka Banteng Dance as a representation of the spirit of freedom. The Merdeka Bantengan. Dance, one of the important elements in this art, is often associated with the spirit of resistance and freedom. This research uses a qualitative approach. Data was collected through participant observation, in-depth interviews with artists and cultural figures, as well as studying related literature. The analysis was carried out using thematic analysis and semiology methods to understand the symbolism contained in dance movements, costumes and music. The research results show that the Merdeka Bantengan Dance reflects the ideology of freedom through the use of the Bantengan symbol as a representation of strength and resistance to oppression. Through cultural and ideological meaning, the Merdeka Banteng Dance becomes a means of communication and expression of the spirit of freedom that is rooted in Bantengan art. This research provides new insight into how traditional art can function as a mirror of ideology and become a means of social expression in society.   Kesenian Bantengan, sebagai bagian dari budaya tradisional Jawa Timur, tidak hanya berfungsi sebagai hiburan, tetapi juga sebagai media ekspresi sosial dan ideologis yang sarat makna simbolis. Penelitian ini bertujuan untuk menganalisis hubungan antara kesenian Bantengan dengan ideologi kebebasan, dengan fokus pada Tari Banteng Merdeka sebagai representasi spirit kebebasan. Tari Banteng Merdeka, salah satu elemen penting dalam kesenian ini, sering diasosiasikan dengan semangat perlawanan dan kebebasan. Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam dengan para pelaku kesenian dan budayawan, serta studi literatur terkait. Analisis dilakukan dengan menggunakan metode analisis tematik dan semiologi untuk memahami simbolisme yang terkandung dalam gerakan tari, kostum, dan musik. Hasil penelitian menunjukkan bahwa Tari Banteng Merdeka merefleksikan ideologi kebebasan melalui penggunaan simbol banteng sebagai representasi kekuatan dan perlawanan terhadap penindasan. Melalui pemaknaan budaya dan ideologis, Tari Banteng Merdeka menjadi sarana komunikasi dan ekspresi dari semangat kebebasan yang mengakar dalam kesenian Bantengan. Penelitian ini memberikan wawasan baru mengenai bagaimana seni tradisional dapat berfungsi sebagai cermin ideologi dan menjadi alat ekspresi sosial dalam masyarakat.